Pengaruh Perubahan Tekanan Vakum Terhadap Kinerja Kondensor PLTU Ni Tanasa Unit 1 - Sudia, Budiman; Samhuddin, Samhuddin; Aminur, Aminur; Gunawan, Yuspian; Imran, Nur Al (Jurusan Teknik Mesin, Universitas Halu Oleo, 2024)
The condenser is a heat exchange device with the function of condensing the steam coming out of the low-pressure turbine into water. As the condenser is one of the main components of a PLTU, the effectiveness of the condenser greatly influences the efficiency of the PLTU. One of the variables that determines condenser performance is changes in vacuum pressure. This change in vacuum pressure often occurs as long as the PLTU is operating. This study aims to determine the effect of changes in condenser vacuum pressure on condenser performance at PLTU Ni Tanasa Unit 1. Data collection was carried out at peak load conditions via the Central Control Room (CCR). The analysis results show that a decrease in vacuum pressure affects condenser performance. The variables that influence condenser performance are the heat transfer coefficient and maximum heat transfer. The maximum heat transfer coefficient is U = 383.32 W/m2.oC and maximum condenser effectiveness is e = 0.941, occurs at a vacuum pressure of 89.8 kPa, the maximum heat transfer rate is Q ̇=2584.5 kJ/s, occurs at condenser pressure 90.4 kPa. Keywords: pressure, vacuum, rate of heat transfer, effectiveness, condenser